2007
DOI: 10.2511/rpsd.32.4.247
|View full text |Cite
|
Sign up to set email alerts
|

The Cumulative Cost-Effectiveness of Supported and Sheltered Employees with Mental Retardation

Abstract: This study investigated the cumulative costs generated by supported and sheltered employees with mental retardation throughout one Bemployment cycle,[ that is, from the moment they entered their respective programs to when they exited or stopped receiving services. Data indicate that supported employees acquired services costing funding sources a total of $6,619 over 5.98 fiscal quarters or a per fiscal quarter cost of $1,107. In comparison, sheltered employees acquired services costing funding sources a total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…However, to date, there have been very few direct costcomparisons of sheltered and supported employment. Moreover, the two cost-analysis studies that are available [11,4] may have compared supported and sheltered employees with vastly different characteristics and service needs. Consequently, their findings may not be accurate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, to date, there have been very few direct costcomparisons of sheltered and supported employment. Moreover, the two cost-analysis studies that are available [11,4] may have compared supported and sheltered employees with vastly different characteristics and service needs. Consequently, their findings may not be accurate.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research identified similar disparities. For example, Cimera [4] found that sheltered employees received services costing nearly three times what supported employees received.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Change is an essential component to doing business differently, including (a) responding to the expectation of persons with disabilities that they will work (National Longitudinal Transition Survey, 2008;Migliore, Grossi, Mank, & Rogan, 2008), (b) recognizing the evolving labor market needs (Occupational Outlook Handbook, 2010-2011), (c) acknowledging the need to allocate public resources in a cost effective fashion (Cimera, 2007), (d) providing services that lead to outcomes that support increased economic self-sufficiency , and (e) redirecting resources (personnel, funding, and even psychic energy) to support those that respond to the expectations and preferences …”
Section: What Is Competitive Integrated Employment?mentioning
confidence: 99%